Using the completing-the-square method, rewrite f(x) = x2 − 6x + 2 in vertex form.

f(x) = (x − 3)2
f(x) = (x − 3)2 + 2
f(x) = (x − 3)2 − 7
f(x) = (x − 3)2 + 9

Respuesta :

[tex]f(x)=x^{2}-6x+2 \\ \\ x^{2}-6x+2 = x^{2}-6x+9-7=(x-3)^{2}-7 \\ \\ f(x)=(x-3)^{2}-7[/tex]

Answer:C. f(x) = (x − 3)2 − 7

Using the completing-the-square method, rewrite f(x) = x2 − 6x + 2 in vertex form.

A. f(x) = (x − 3)2

B. f(x) = (x − 3)2 + 2

C. f(x) = (x − 3)2 − 7

D. f(x) = (x − 3)2 + 9

Step-by-step explanation:

I just did the assignment and the correct answer is C. f(x) = (x − 3)2 − 7! Hope this helps.

Good Luck!!